Femtosecond-written volume Bragg gratings in fluoride glasses - Talbot, Lauris; Richter, Daniel; Heck, Maximilian; Nolte, Stefan; Bernier, Martin (Optics Letters, 2020)
We report on whatwe believe are the first volume Bragg gratings written inside bulk multicomponent fluoride glasses. The gratings inscribed with tightly focused infrared (IR)-femtosecond pulses in combination with the phase-mask technique exhibit refractive index modulations of up to 5×10-4 with reflectivities up to 90% at a wavelength near 2.8 μm. Such highly compact and narrowband filters could have a significant impact on numerous high-end applications from the UV to the mid-IR.
CRIS-Team Scopus Importer:2023-04-20